EVALUATION OF TAX AMNESTY POLICY IN AN EFFORT TO INCREASE TAX REVENUE - Chairil Anwar Pohan; Mega Kusuma; Pebriana Arimbhi (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
This study aims to analyze Tax Amnesty in an effort to increase tax revenues, in conformity with the theory/rules/principles of Taxes, and to analyze taxpayer compliance in paying taxes in the framework of Tax Amnesty in reporting business activities and paying taxes. The method that will be used in this study is a qualitative descriptive research method. The technique of collecting data is done by in-depth interviews, observations, literature studies and documentation. The aim of the tax amnesty is to accelerate growth and economic restructuring through the transfer of property, which will have an impact on increasing domestic liquidity, improving the Rupiah exchange rate, decreasing interest rates and increasing investment. Encouraging tax reform towards a more just taxation system and the expansion of a more valid, comprehensive and integrated taxation database, in addition to increasing tax revenues is also another goal of tax amnesty. The government's efforts to attract public funds that have been parked in other countries' banks are the goal of tax amnesty, but unfortunately despite various efforts to build the willingness of taxpayers to join the Tax Amnesty, some taxpayers only declare their assets but the funds are not repatriated to Indonesia. On the other hand, the realization of ransom receipts did not reach the target. Therefore post-tax amnesty policy needs to be strengthened by tax audits and the implementation of AEoI.